A Multivariable Index for Grading Exercise Gas Exchange Severity in Patients with Pulmonary Arterial Hypertension and Heart Failure - Kim, Chul-Ho; Anderson, Steve; MacCarter, Dean; Johnson, Bruce (Pulmonary Medicine, 2012)
Patients with pulmonary arterial hypertension (PAH) and heart failure (HF) display many abnormalities in respiratory gas exchange. These abnormalities are accentuated with exercise and track with disease severity. However, use of gas exchange measures in day-to-day clinical practice is limited by several issues, including the large number of variables available and difficulty in data interpretation. Moreover, maximal exercise testing has limitations in clinical populations due to their complexity, patient anxiety and variability in protocols and cost. Therefore, a multivariable gas exchange index (MVI) that integrates key gas exchange variables obtained during submaximal exercise into a severity score that ranges from normal to severe-very-severe is proposed. To demonstrate the usefulness of this index, we applied this to 2 groups (PAH, n=42 and HF, n=47) as well as to age matched healthy controls (n=25). We demonstrate that this score tracks WHO classification and right ventricular systolic pressure in PAH (r=0.53 and 0.73, P≤0.01) and NYHA and cardiac index in HF (r=0.49 and 0.74, P≤0.01). This index demonstrates a stronger relationship than any single gas exchange variable alone. In conclusion, MVI obtained from light, submaximal exercise gas exchange is a useful approach to simplify data interpretation in PAH and HF populations.